1996
DOI: 10.1002/(sici)1097-0215(19960516)66:4<532::aid-ijc18>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

LY-6C+ natural T (NT) cells mediate immune surveillance against NK-sensitive and NK-resistant transplantable tumours in certain strains of mice

Abstract: We have previously shown that anti-Ly-6C monoclonal antibody (MAb) 2B6-F2 identifies a subset of (CBA % o 1996 Wiley-Liss, Inc.C57BL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…It is interesting that mice deficient in Apo E have increased susceptibility to LPS endotoxemic shock [41]. Ly-6C, which is expressed on multiple cell types including macrophages, endothelial, natural killer (NK), and T cells, has been associated with NK cell cytotoxicity [42][43][44][45]. Cofilin is an actin-binding protein important in actin-filament depolymerization crucial in motility and capping [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that mice deficient in Apo E have increased susceptibility to LPS endotoxemic shock [41]. Ly-6C, which is expressed on multiple cell types including macrophages, endothelial, natural killer (NK), and T cells, has been associated with NK cell cytotoxicity [42][43][44][45]. Cofilin is an actin-binding protein important in actin-filament depolymerization crucial in motility and capping [46].…”
Section: Discussionmentioning
confidence: 99%
“…Other NK-sensitive targets, including the Fas 1 Jurkat and Fas 2 B16, were also susceptible to Ly-6C 1 splenocyte killing. We have recently shown that Ly-6C 1 cells are also responsible for the immunosurveillance against B16 transplanted into mice (Martiniello et al, 1996). Furthermore, our data suggest that multiple killing mechanisms are utilized by NT cells.…”
Section: Was Responsible For Yac-1 Lysismentioning
confidence: 60%